A Border Strategy Analysis of Ad Source and Message Tone in Senatorial Campaigns - Wang, Yanwen; Lewis, Michael; Schweidel, David A. (Marketing Science, 2018)
Political advertising is controversial, as there is widespread concern about money from political action committees (PACs and super PACs) distorting the democratic process. Studying advertising effectiveness is, however, a challenging topic for several reasons, including the endogenous nature of fundraising and ad spending rates. However, the extensive use of targeting based on designated marketing areas (DMAs) creates a setting in which neighboring counties with comparable demographics receive different levels of advertising exposure. In this paper, we leverage these advertising discontinuities along DMA borders to study the relative effectiveness of political advertising on vote shares and turnout rates in 2010 and 2012 senatorial elections. We find that negative advertising sponsored by PACs is significantly less effective than that sponsored by candidates in affecting two-party vote shares and voter turnout. A 1% increase in negative advertising by the candidate produces a significant 0.015% lift in the candidate’s unconditional vote shares. By contrast, negative advertising from PACs is ineffective in increasing its supported candidate’s unconditional vote share. Further analysis reveals that the competitiveness of races moderates the effectiveness of political advertising, providing implications for those managing candidates’ campaigns, PACs, and super PACs. Data and the online appendix are available at https://doi.org/10.1287/mksc.2017.1079 .